2019
DOI: 10.2135/cropsci2018.10.0626
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Diet Preference of Novel Endophyte‐Infected Tall Fescue Cultivars

Abstract: A fungal endophyte, Epichloë coenophiala (Morgan‐Jones & W. Gams) C.W. Bacon & Schardl, naturally infects tall fescue [Lolium arundinaceum (Schreb.) Darbysh.]. The common, toxic endophyte produces ergot alkaloids that cause the livestock disorder known as tall fescue toxicosis. Strains of E. coenophiala that produce little or no toxic ergot alkaloids are referred to as “novel” endophyte associations and offer a solution to tall fescue toxicosis. The objective of this study was to determine differences in anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Our results showed it was possible to interseed annual warm‐season grasses in each environment (particularly humid pasturelands) without suppressing or partially killing the perennial if harvested after primary tillers elongated and flowered in spring. A challenge to interseeding tall fescue stands harvested after primary tillers elongate and flower in spring (Table 2) would likely be the presence of a fungal endophyte, Epichloë coenophiala (Morgan‐Jones and Gams) Bacon and Schardl, that lives in mutualism with the plant but produces toxic ergot alkaloids (Dillard, Smith, & Hancock, 2019; Kenyon et al., 2018; Kenyon et al., 2019). Large variability in ergot alkaloid content occurs across years, within seasons, and between cultivars (Dillard et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed it was possible to interseed annual warm‐season grasses in each environment (particularly humid pasturelands) without suppressing or partially killing the perennial if harvested after primary tillers elongated and flowered in spring. A challenge to interseeding tall fescue stands harvested after primary tillers elongate and flower in spring (Table 2) would likely be the presence of a fungal endophyte, Epichloë coenophiala (Morgan‐Jones and Gams) Bacon and Schardl, that lives in mutualism with the plant but produces toxic ergot alkaloids (Dillard, Smith, & Hancock, 2019; Kenyon et al., 2018; Kenyon et al., 2019). Large variability in ergot alkaloid content occurs across years, within seasons, and between cultivars (Dillard et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Large variability in ergot alkaloid content occurs across years, within seasons, and between cultivars (Dillard et al., 2019). It will be important to test fields for ergot alkaloid content to determine risk of cutting and feeding hay (Dillard et al., 2019) and consider replanting with a novel endophyte‐infected tall fescue cultivar that produces little or no toxic ergot alkaloids (Kenyon et al., 2019). Cutting tall fescue while vegetative at a stubble height >5 cm to increase the proportion of leaf blade would also reduce ergot alkaloid concentrations (Kenyon et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, "Monad" wheat (Triticum aestivum) infected with an Epichloë strain sourced from Elymus dahuricus subspecies excelsus-strain AR3060 were stunted or dwarfed [47]. Moreover, Kenyon [48] observed no differences in annual dry matter (DM) production for E− and E+ tall fescue. This indicates that Epichloë is triggering some form of host response, and this response varies according to the genotype of the individual host plant.…”
Section: Endophyte Status and Barley Cultivar Affect Barley Growth Pa...mentioning
confidence: 99%
“…Many studies have shown the benefits of Epichloë endophytes in agricultural systems; however, most studies focused on major pasture grass species (Johnson et al, 2013 ; Le Cocq et al, 2017 ; Kenyon et al, 2019 ). For example, several Epichloë endophyte strains (i.e., MaxQ ® , MaxP ® , AR1, and AR37) have been used to artificially inoculate tall fescue and perennial ryegrass with similar benefits, which have been successfully commercialized in New Zealand, South America, Australia, and the United States (Johnson et al, 2013 ; Young et al, 2013 ; Lugtenberg et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%